Staphylococcus epidermidis Biofilms Have a High Tolerance to Antibiotics in Periprosthetic Joint Infection - John A. Koch (Life, 2020)
Both Staphylococcus aureus and Staphylococcus epidermidis are commonly associated with periprosthetic joint infections (PJIs). The treatment of PJI can be challenging because biofilms are assumed to have an increased intolerance to antibiotics. This makes the treatment of PJI challenging from a clinical perspective. Although S. aureus has been previously demonstrated to have increased biofilm antibiotic tolerance, this has not been well established with Staphylococcus epidermidis. A prospective registry of PJI S. epidermidis isolates was developed. The efficacy of clinically relevant antibiotics was quantified against these isolates. S. epidermidis planktonic minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were collected using clinical laboratory standard index (CLSI) assays for eight antibiotics (doxycycline, vancomycin, daptomycin, clindamycin, rifampin, nafcillin, and trimethoprim/sulfamethoxazole). Mature biofilms were grown in vitro, after which minimum biofilm inhibitory concentration (MBIC) and minimum biofilm bactericidal concentration (MBBC) were quantified. Only rifampin and doxycycline had a measurable MBIC across all tested isolates. Based on MBBC, 64% of S. epidermidis biofilms could be eliminated by rifampin, whereas only 18% by doxycycline. S. epidermidis biofilm was observed to have a high tolerance to antibiotics as compared to planktonic culture. Isolate biofilm antibiotic tolerance varied to a larger degree than was seen in planktonic cultures.